Influence of Tin Doped TiO2 Nanorods on Dye Sensitized Solar Cells - Sandeep B. Wategaonkar (MDPI AG, 2021)
The one-step hydrothermal method was used to synthesize Sn-doped TiO2 (Sn-TiO2) thin films, in which the variation in Sn content ranged from 0 to 7-wt % and, further, its influence on the performance of a dye-sensitized solar cell (DSSC) photoanode was studied. The deposited samples were analyzed by X-ray diffraction (XRD) and Raman spectroscopy, which confirmed the existence of the rutile phase of the synthesized samples with crystallite size ranges in between 20.1 to 22.3 nm. In addition, the bare and Sn-TiO2 thin films showed nanorod morphology. A reduction in the optical band gap from 2.78 to 2.62 eV was observed with increasing Sn content. The X-ray photoelectron spectroscopy (XPS) analysis confirmed Sn4+ was successfully replaced at the Ti4+ site. The 3-wt % Sn-TiO2 based DSSC showed the optimum efficiency of 4.01%, which was superior to 0.87% of bare and other doping concentrations of Sn-TiO2 based DSSCs. The present work reflects Sn-TiO2 as an advancing material with excellent capabilities, which can be used in photovoltaic energy conversion devices.